Effects of short-term multi-pollutant exposure on the oxidative stress status of captive songbirds - Ziegler, Ann Kathrin; Rissler, Jenny; Gudmundsson, Anders; Isaksson, Caroline ; 0000-0002-6889-1386 (Functional Ecology, 2025)
The human influence on Earth's ecosystems is omnipresent. Artificial light at night (ALAN), anthropogenic noise, and air pollution are inherent features of human activities and infrastructure and pose novel environmental challenges to urban-dwelling wildlife. So far, most of the studies investigating the impacts of exposure to urban pollutants on animals have either investigated the effects of urban environments per se or of single pollutants. However, urban pollutants co-occur, and interactive effects may arise when acting in combination, but we lack a deeper understanding of the effects of combined exposures. Here, we experimentally exposed captive zebra finches Taeniopygia guttata in a full-factorial design to increased levels of ALAN, anthropogenic noise and/or soot and measured oxidative stress status in blood before and after a 5-day exposure. We found that the combined exposure to ALAN and noise led to a positive synergistic effect (higher levels than the sum of individual effects) on the antioxidant glutathione and a negative synergistic effect (lower levels than the sum of individual effects) on the levels of oxidative damage, measured as the concentration of reactive oxygen metabolites. Soot had no effect on the avian oxidative stress status in the blood immediately after the exposure, neither singly nor in combination with other pollutants. To conclude, our results indicate that a combination of stressors can have complex non-additive interactive effects on oxidative stress status after a short-term exposure. Surprisingly, a combined exposure to ALAN and anthropogenic noise leads to a stronger antioxidant response that seems to prevent oxidative damage than exposure to only one of the stressors. Whether the increased antioxidant defence entails any long-term costs remains to be determined in future studies. Read the free Plain Language Summary for this article on the Journal blog.
Keywords: antioxidants; artificial light at night (ALAN); oxidative damage; soot; traffic noise; urbanization; zebra finch